2016
DOI: 10.1016/j.ijrobp.2016.06.231
|View full text |Cite
|
Sign up to set email alerts
|

An Independently Validated Nomogram for Individualized Estimation of Survival Among Patients With Newly Diagnosed Glioblastoma: NRG Oncology/RTOG 0525 and 0825

Abstract: to profile 800 human miRNAs in each sample. Univariate (UVA) and multivariate (MVA) Cox regression analyses were performed using progression-free survival (PFS) and overall survival (OS) as clinical endpoints. Results: In our UVA, we identified 10 miRNAs that were significantly associated with PFS (P value < 0.05), however, no miRNAs had a false discover rate (FDR) P value < 0.2. Thirty-nine miRNAs were significantly predictive of OS (P value < 0.05) and 9 had a FDR P value < 0.2. Upon MVA, adjusting for age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 0 publications
3
23
1
Order By: Relevance
“…Finally, adding therapeutic information led to a further increase in prognostic performance for OS and PFS with a higher predictive performance compared to the formerly proposed nomogram by Gittleman et al 26 Kaplan-Meier survival analysis showed a significant separation of high-risk from low-risk patients for the OS model.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Finally, adding therapeutic information led to a further increase in prognostic performance for OS and PFS with a higher predictive performance compared to the formerly proposed nomogram by Gittleman et al 26 Kaplan-Meier survival analysis showed a significant separation of high-risk from low-risk patients for the OS model.…”
Section: Discussionmentioning
confidence: 91%
“…The recently proposed nomogram from the work of Gittleman et al 26 was tested on the independent test set using the 12-month survival probabilities. It achieved a predictive performance with an AUC of 0.64 in comparison with AUCs of 0.75 and 0.80 for models M6 and M7.…”
Section: Prediction Of Patients' Osmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Haley et al. used gender for analysis and found that age at diagnosis, KPS, EOR and MGMT promoter methylation status were all prognostic factors ( 16 ). Then, they added concurrent chemoradiotherapy and confirmed its predictive value in a subsequent nomogram of a wild type IDH nGBM cohort ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…The nomogram was first developed to identify new prognostic factors for survival in 2008 by Thierry Gorlia ( 15 ). Other established nomograms have since been widely used to predict prognosis in GBM ( 16 , 17 ). Although these nomograms presented good prediction capacity, they did not include EOR-NCE for analysis.…”
Section: Introductionmentioning
confidence: 99%